cyclic AMP Regulation and Its Command in the Pacemaker Channel HCN4 - Porro, Alessandro; Thiel, Gerhard; Moroni, Anna; Saponaro, Andrea (Frontiers in Physiology, 2020)
Direct regulation of the pacemaker “funny” current (If) by cAMP underlies heart rate modulation by the autonomic nervous system. At the molecular level, cAMP activates Hyperpolarization-activated Cyclic nucleotide-gated channels (HCN) that drive If in sinoatrial node myocytes. Even though HCN channel genes were identified more than 20 years ago, the understanding of how cAMP regulates their gating is still fragmented. Here we summarize present understanding on how the cAMP signal is transmitted from the cytosolic to the transmembrane domain in HCN4. We further discuss how detailed structural knowledge prompted the development of pharmacological/genetic tools for the control of cAMP regulation in these channels.